Determinants of the efficiency of carbon tax implementation in Algeria? Diagnosing the world-leading Swedish experience - dahdouh, nabil; boubaya, hacene (Journal of Research in Finance and Accounting, 2024)
This study aims to provide an objective reading of the determinants of implementing the carbon tax in Algeria as a tool to reduce greenhouse gas emissions that cause global warming, by identifying the nature of the tax, the determinants of its design and selection of its price, the motives and justifications for its application and its effects on the economy in Algeria, In addition to studying the effectiveness of applying a carbon tax because of its importance in reducing carbon emissions on the Algerian environment, despite the advantages of this type of taxation, it may result in negative effects on economic growth and international competitiveness in the short term.This paper outlines Sweden's experience in implementing a carbon tax on fossil fuels used for transportation, heating and industrial processes, the resulting reduction in carbon emissions while maintaining a strong economy, and the potential for Algeria to benefit from the experience